Debt Management Performance Assessment : Yemen - World Bank (World Bank, Washington, DC, 2020)
From October 16 to 26, 2010, a World Bank team undertook a debt management performance assessment (DeMPA) mission to Sana‘a, Yemen. The objective was to undertake a comprehensive assessment of debt management functions applying the DeMPA tool. The assessment reveals that Yemen exceeds minimum requirements for effective debt management performance as specified by the DeMPA tool with respect to the managerial structure underpinning debt management operations; the level of disclosure and evaluation of debt management activities to the Parliament; the conduct of external audits of debt management activities; the availability of key fiscal variables for the autonomous preparation of a periodic debt sustainability analysis; and the meeting of statutory requirements to report on central government debt.